Environmental impact assessment procedures for projects in marine environment evaluation analysis - Runko Luttenberger, Lidija; Matić, Jadranka, geologinja; Mihelić, Draga; Mandić, Nikola, inženjer prometa (2020)
Appropriately high level of marine environment protection implies taking the measures of prudence, precaution, reasonable and rational use of marine natural resources, and that is achieved also through the assessment of potential significant negative impacts at the early stage of planning of a particular project. Marine fish and shellfish farms, marine ports, minerals exploitation, shore nourishment, seabed deepening and drying, construction in and at the sea and other projects in marine environment are subject to implementation of environmental impact assessment and screening projects based on environmental reports. The description of main features of technological processes of planned projects and their impact on marine environment constitute an integral part of environmental reports, as technical baselines for assessing potential significant negative impacts. In order to prevent pollution, pursuant to law provisions, it is necessary to apply technologies that are most efficient for achieving high level of marine environment protection. In assessing at the planning stage whether most acceptable technologies are used, consultative expert committee consisting of scientists and professionals is engaged in environmental impact assessment procedures. Paper analyses the parts of environmental reports describing technological procedures and proposes the methods of upgrading their quality by involving experts and scientists in examining thereof.
Bibliografija: 16 jed.
Abstract.
Keywords: Morski okoliš -- Procjena utjecaja na okoliš -- Morske tehnologije